Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fimmu.2021.626255
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Role of BET Bromodomain Proteins BRD2 and BRD4 in Human NK Cell Function

Abstract: Natural killer (NK) cells are innate lymphocytes that play a pivotal role in the immune surveillance and elimination of transformed or virally infected cells. Using a chemo-genetic approach, we identify BET bromodomain containing proteins BRD2 and BRD4 as central regulators of NK cell functions, including direct cytokine secretion, NK cell contact-dependent inflammatory cytokine secretion from monocytes as well as NK cell cytolytic functions. We show that both BRD2 and BRD4 control inflammatory cytokine produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 61 publications
(76 reference statements)
0
12
0
Order By: Relevance
“…We found that NK cells treated with butyrate expressed higher levels of the BET bromodomain containing protein, BRD2. BRD2 controls inflammatory cytokine production by NK cells 34 . We also found that NK cells differentially express the ubiquitin-binding selective autophagy receptor p62/SQSTM1, and the RNA helicase DDX21 following butyrate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We found that NK cells treated with butyrate expressed higher levels of the BET bromodomain containing protein, BRD2. BRD2 controls inflammatory cytokine production by NK cells 34 . We also found that NK cells differentially express the ubiquitin-binding selective autophagy receptor p62/SQSTM1, and the RNA helicase DDX21 following butyrate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, silencing of BET proteins by small interfering RNA reduced TNF-α expression in HC and RA monocytesderived macrophages [59]. Cribbs et al have also showed that monocytes reduced TNF-α production upon co-culture with NK cells stimulated with BET inhibitor JQ1 [60]. Similarly, the immune complex-mediated activation of monocytes was reduced by JQ1 in the lupus model with MRL-lpr mice [61].…”
Section: Role Of Histone Modificationmentioning
confidence: 98%
“…IL7R encodes a receptor for interleukin 7 (IL7) and IL‐7 signaling is critical for the development and maintenance of the entire lymphoid compartment 47 . BRD2 controls inflammatory cytokine secretion in NK cells 48 . IRF‐2 was involved in the production and maturation of NK cells 49 .…”
Section: Resultsmentioning
confidence: 99%